The Role Of The Consumer Organisations in England and Turkey on Consumer Protection - Günal, Aydın Ebrar (Fırat Üniversitesi, 2023)
It is required that the consumers must become self aware and they must make their voice heard with an effective consumer movement; to raise awareness about claiming their rights, in terms of protecting themself against the processes that they are a party to and the practices that they encounter before, during and after the process; to make healthy choices while getting a product or a service; to be a direct stakeholder to develop consumer policies that meet their needs. In this context, the existence of organized consumer movements is very important for the protection of financially weak consumers. Individuals can be a party to many legal transactions and practices in the goods and services markets. It is important to determine the parties and the nature of the legal proceedings in order to draw the limits of the rights held in terms of consumer protection. In this context, modern studies on consumer protection have emerged primarily in developed countries, and international unions and organizations, state and public institutions, consumers and consumer organizations established by consumers have played an important role in ensuring the developments. In our study, primarily it is revealed that the universal development of the consumer rights that includes the right of organization, than the consumer organizations that have been established in the UK and Turkey by consumers in-person and this civil societies’ role in protecting consumers are examined.

Tüketicilerin taraf olduğu işlemler ile işlem öncesi, sırası ve sonrasında karşılaştığı uygulamalara karşı kendini koruyabilmesi bakımından kendilerinde hak arama bilincinin oluşturulabilmesi, bir ürün veya hizmeti edinirken seçimlerini sağlıklı yapabilmesi, ihtiyaçlarına cevap verir tüketici politikalarının geliştirilmesinde doğrudan paydaş olabilmesi için etkili bir tüketici hareketi ile bilinçlenerek kendi sesini duyurması gerekmektedir. Bu çerçevede mali açıdan da zayıf konumda olan tüketicinin korunması için, örgütlenmiş tüketici hareketlerinin varlığı büyük önem arz etmektedir. Kişiler mal ve hizmet piyasalarında birçok hukuki işlem ile uygulamanın tarafı olabilmektedir. Tüketicinin korunması bakımından sahip olunan hakların sınırının çizilmesi için hukuki işlemlerin taraflarının ve niteliğinin belirlenmesi önem arz etmektedir. Bu çerçevede tüketicinin korunmasına ilişkin modern anlamda çalışmalar başta gelişmiş ülkelerde ortaya çıkmış olup, uluslararası birlik ve örgütler, devlet ve kamu kuruşları, tüketiciler ve tüketiciler tarafından kurulan tüketici örgütleri gelişmelerin sağlanmasında önemli rol oynamıştır. Çalışmamızda öncelikle örgütlenme hakkının da içerisinde olduğu evrensel tüketici haklarının gelişimi ortaya konularak, İngiltere ve Türkiye’de tüketicilerin bizzat kurdukları tüketici örgütleri ile bu sivil toplum yapılanmalarının tüketicinin korunmasındaki rolleri incelenmiştir.
İNGİLTERE VE TÜRKİYE’DE TÜKETİCİ ÖRGÜTLERİNİN TÜKETİCİNİN KORUNMASINDAKİ ROLÜ